The Mediators of Collegial Solidarity on Job Performance: A Relational Study in the Education Sector - İbrahim Hakan Karataş; Bilal Çankır (İnsan & Toplum)
One of the distinguishing features of educational institutions is that the learning and teaching processes that are at their core are mostly carried out by expert educators independently on their own in the classroom. This state of independence and solitude causes collegial solidarity to emerge as a more important issue for educational institutions when compared to other institutions. This study examines the mediators of the relationship between educators’ collegial solidarity and job performance. This study examines the mediating roles of three individual variables (i.e., thriving at work, self-efficacy, and work engagement) and three institutional variables (i.e., collegial relations, administrative support, and organizational climate) have on the relationship between educators’ collegial solidarity and job performance using data collected from a total of 766 participants working at educational institutions. It has been determined that institutional and individual variables have a mediating effect in the relationship between educators’ colleague solidarity and job performance. It was observed that institutional variables had a weaker mediating effect than individual variables in this effect. This result shows that the unique nature of the education profession reveals a different structure in terms of the variables examined in the research.